Pembekalan Asesmen Pembelajaran Untuk Meningkatkan Profesionalisme Guru - Triwiyono , Triwiyono; Pieter, Jan; Risamasu, Putu Victoria M.; Inggamer, Mamberuman Marthen (Bakti Hayati: Jurnal Pengabdian Indonesia, 2023)
This community service activity was carried out because it was found that teachers' knowledge about assessment was still low. The aim of this activity is (1) to increase teachers' knowledge about learning assessment, (2) to provide provisions for teachers in designing learning assessments. The participants in the activity were 23 teachers from the Sekolah Dasar Negeri Inpres Perumnas I Waena, Jayapura City, totaling 23 people. The methods used are lectures, discussions and questions and answers. To measure the increase in participants' knowledge, a pretest and posttest were carried out, while the success of the activity was determined by giving a questionnaire to all participants. The results of the activity showed that teachers’ assessment knowledge increased after the debriefing was carried out, this was indicated by an average pretest score of 36.65 and an average posttest score of 77.39 and participants gave a positive response to the implementation of the activity.